Optimization of Process Parameters of Composite Wicked Heat Pipe - Sateesh N.; Nookaraju B.Ch.; Subbiah Ram; Kumar Avnish; Jayahari L. (E3S Web of Conferences, 2023)
Heat pipe is used to extract heat generated from a surface and applicable to cooling of the many components. Some of the main applications of heat pipes are space crafts, computer systems, permafrost cooling, heat exchangers and thermal storage sub systems. In this work, an experiment will be carried out with an indirect heat composite pipe located with different orientation, heat input and mass flow. Thermal resistance, heat transfer coefficient and thermal efficiency are determined, which are applicable for laptop cooling and solar heating. Heat input 25 to 150 watts, with orientation angles 0, 30, 45, 90 degrees, mass flow rate are 0.01kg/sec, 0.02kg/sec and 0.03kg/sec are considered.